INNOVATION AND IT AS CROSS-CUTTING DRIVERS OF COMPETITIVENESS IN MEXICO (International Seven Journal of Multidisciplinary, 2025)
The competitiveness of any country's economic entities in the era of knowledge management, the use of performance metrics, and scientific management, which define the IT industry and also characterize it, according to IMCO and AIMSI. It is in this context that strategic plans revalue the role of their human capital and its impact on the assets of social and productive organizations.